2007
DOI: 10.1007/s00402-007-0397-5
|View full text |Cite
|
Sign up to set email alerts
|

A giant extrasynovial osteochondroma in the infrapatellar fat pad: end stage Hoffa’s disease

Abstract: The infrapatellar fat pad of Hoffa is commonly injured but rarely discussed in the orthopaedic literature. Hoffa's disease is the extension of various traumatic events due to impingement and inflammation of the infrapatellar fat pad and known as a vague reason for anterior knee pain. Inflammation is foreground during acute phase of the disease while impingement due to fibrosis and scar tissue of infrapatellar fat pad plays a major role in the chronic phase. The osteochondroma of the infrapatellar fat pad secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
0
46
1
Order By: Relevance
“…This leads to differentiation into osteochondroma, which is however rare. 9 A study by Ushiyama et al 11 showed that this IFP has endocrine functions. It was found that cytokines involved in chondrocyte metabolism are produced in IFP, such as the basic fibroblast growth factor, vascular endothelial growth factor, tumor necrosis factor-alpha and interleukin-6.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This leads to differentiation into osteochondroma, which is however rare. 9 A study by Ushiyama et al 11 showed that this IFP has endocrine functions. It was found that cytokines involved in chondrocyte metabolism are produced in IFP, such as the basic fibroblast growth factor, vascular endothelial growth factor, tumor necrosis factor-alpha and interleukin-6.…”
Section: Discussionmentioning
confidence: 97%
“…These include Hoffa's disease, IFP ossification, solitary intraarticular chondroma, acquired intra-articular osteochondroma, intracapsular chondroma, para-articular chondroma/osteochondroma and capsular osteoma. 9 In Hoffa's syndrome, there is increased T 2 sequence signal due to edema and hemorrhage in MRI during the acute phase; and fibrin and hemosiderin build-up during the chronic phase. This is visualized as reduced T 1 and T 2 signals and a hypointense image on MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACL-R). Fibrosis of IPFP tissue could play a major role in the chronic phase of inflammatory diseases [26]. Fibrosis results from the accrual of extracellular matrix components due to excessive synthesis of collagens I, III, and VI, and impaired degradation of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 Patients may have abnormal scar formation. Fracture may occur in approximately 5% of bones with osteochondroma.…”
mentioning
confidence: 99%